2019
DOI: 10.1007/s00167-019-05649-2
|View full text |Cite
|
Sign up to set email alerts
|

Compliance in post-operative rehabilitation is a key factor for return to sport after revision anterior cruciate ligament reconstruction

Abstract: Purpose To assess the rate of return to sport (RTS) following revision Anterior Cruciate Ligament Reconstruction (ACLR) in a rehabilitation-based cohort of patients. A secondary goal of the study was to evaluate the association between compliance in post-operative rehabilitation and RTS rate. Methods The study cohort included 79 sport-active patients (62 males, 17 females, 30.0 ± 10.2 years old) who underwent revision ACLR surgery and followed the same functional-oriented rehabilitation protocol. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 35 publications
1
24
0
1
Order By: Relevance
“…11 Positive associations between adherence to ACLR programs and clinical outcomes have been documented in several studies. 6,14,21 This is consistent with the results of this current study that found the higher the patients’ perception for the importance of home program/self-practice, the better the outcome after hip arthroscopy for FAIS.…”
Section: Discussionsupporting
confidence: 91%
“…11 Positive associations between adherence to ACLR programs and clinical outcomes have been documented in several studies. 6,14,21 This is consistent with the results of this current study that found the higher the patients’ perception for the importance of home program/self-practice, the better the outcome after hip arthroscopy for FAIS.…”
Section: Discussionsupporting
confidence: 91%
“…There is consensus in contemporary sports medicine literature that the optimal rehabilitation protocol progresses through phases defined by functional goals. 2,8,11,16,18,40,41 The above-noted findings indicate that patients are receiving the majority of their PT in the early postoperative period after ACLR, when the primary goals of rehabilitation include increasing range of motion, decreasing knee effusion, and quadriceps activation exercises. 2,17,30,39 Based on typical rehabilitation guidelines, and data from previous studies 2,12,41 detailing rehabilitation after ACLR, this distribution of PT visits suggests that later-stage therapy goals (sports-specific training) may not be sufficiently addressed.…”
Section: Discussionmentioning
confidence: 97%
“…A more external focus also creates an understanding of the applicability of the movement, shifting motivation from extrinsic (outcome-oriented) to intrinsic (inherent satisfaction), which is important for adherence [ 23 ]. Adherence may then also influence physical outcomes by virtue of having performed the exercises [ 24 ].…”
Section: Introductionmentioning
confidence: 99%